RESTORE ME: a RCT of oxaloacetate for improving fatigue in patients with myalgic encephalomyelitis/chronic fatigue syndrome - Cash, Alan; Vernon, Suzanne D.; Rond, Candace; Bateman, Lucinda; Abbaszadeh, Saeed; Bell, Jennifer; Yellman, Brayden; Kaufman, David L. (Frontiers in Neurology, 2024)
Background The energy metabolite oxaloacetate is significantly lower in the blood plasma of ME/CFS subjects. A previous open-label trial with oxaloacetate supplementation demonstrated a significant reduction in myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS)-related fatigue. Methods In this follow-up trial, 82 ME/CFS subjects were enrolled in a 3-month randomized, double-blinded, controlled study, receiving either 2,000 mg of oxaloacetate or control per day. The primary endpoints were safety and reduction in fatigue from baseline. Secondary and exploratory endpoints included functional capacity and general health status. Results Anhydrous enol-oxaloacetate (oxaloacetate) was well tolerated at the tested doses. Oxaloacetate significantly reduced fatigue by more than 25% from baseline, while the control group showed a non-significant reduction of approximately 10%. Intergroup analysis showed a significant decrease in fatigue levels in the oxaloacetate group (p = 0.0039) with no notable change in the control group. A greater proportion of subjects in the oxaloacetate group achieved a reduction in fatigue greater than 25% compared to the control group (p < 0.05). Additionally, 40.5% of the oxaloacetate group were classified as “enhanced responders,” with an average fatigue reduction of 63%. Both physical and mental fatigue improved with oxaloacetate supplementation. Conclusion Oxaloacetate is well tolerated and effectively helps reduce fatigue in ME/CFS patients. Clinical trial registration https://clinicaltrials.gov/study/NCT05273372.